2014
DOI: 10.2478/afmnai-2014-0024
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life in Type 2 Diabetic Patients

Abstract: Summary The presence of diabetes mellitus leads to a decrease in life quality in all domains. The aim of our study was to evaluate the quality of life (QOL) in diabetic patients and the factors affecting it in type 2 diabetic mellitus patients. We conducted a cross-sectional study that included 86 patients with type 2 diabetes mellitus, in the territory of the City of Niš. Health-related QOL of patients was measured using the short form survey (SF-36) that produces an 8-scale health profile. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
37
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 34 publications
10
37
1
6
Order By: Relevance
“…We also observed that the most predominant Comorbidity was hypertension [124(49.6%)] and followed by chronic renal failure [46(18.4%)] in diabetic patients. Similar results were seen in the studies by Gautam et al (2009), Wexler et al (2006 and Spasić et al (2014) in diabetes patients the most frequent comorbidity was hypertension. In a study by Acharya et al (2016), it was reported that more than 50% of the total diabetes patients had hypertension and the similar observation is reported in our study.…”
Section: Discussionsupporting
confidence: 78%
“…We also observed that the most predominant Comorbidity was hypertension [124(49.6%)] and followed by chronic renal failure [46(18.4%)] in diabetic patients. Similar results were seen in the studies by Gautam et al (2009), Wexler et al (2006 and Spasić et al (2014) in diabetes patients the most frequent comorbidity was hypertension. In a study by Acharya et al (2016), it was reported that more than 50% of the total diabetes patients had hypertension and the similar observation is reported in our study.…”
Section: Discussionsupporting
confidence: 78%
“…In our study, glycemic control was not associated with HRQoL while patients with complications showed lower QoL scores than patients without complications, though this difference was not statistically significant. Additionally, men with T2DM reported higher scores in present QoL than women, a finding consistent with other studies in similar populations (9,12,(26)(27)(28)(29). Several studies showed that the most negatively impacted domains were those related to food, namely, 'freedom to eat', 'enjoyment of food' and 'freedom to drink'.…”
Section: Discussionsupporting
confidence: 78%
“…On the other hand, however, Spasić, et al, (2014) have found that patients with type 2 diabetes have a lower quality of life in all aspects (physical and mental health components). Sig=.001 and r=.464, Sig=.001, respectively).…”
Section: The Quality Of Lifementioning
confidence: 96%